The efficiency of public spending in education: an evaluation of the Serideo Potiguar region (2008-2015) (Research, Society and Development, 2019)
The public administration aims to reach your goals with the minimum application of public expenditures. The comparing results obtained and the respective financial investments employed favor the construction of the efficient decision-making process well as the rationalization of the use of the resources of the public fund. In the research present it was searched, the efficiency of public expenditures on education in the Initial and Final Years of Primary Education in the Seridó region of Rio Grande do Norte evaluated through the application of the Data Envelopment Analysis (DEA), listing which municipalities appear to be efficient in the executing with education expenditures for the period from 2008 to 2015. The indicated analyzes that 84.6% municipalities of small 1 were efficient in some bienniums of the Elementary School analysis in the Years Initial, and 46.1% had their considered performances efficient in the Final Years, in at least one biennium. In the assessments of Elementary School in the Initial and Final Years of small municipalities 2, similarity was found between the scores efficiency for the units in the intervals of the Initial Years and difference between the performances only in the analyzes of the Final Years, that made the identification possible of the DMU present at the efficiency frontier.